2020
DOI: 10.1021/acs.macromol.9b02388
|View full text |Cite
|
Sign up to set email alerts
|

Single-Chain Janus Nanoparticle by Metallic Complexation

Abstract: Single-chain Janus nanoparticle of the example polymer polystyrene-blockpoly(2-vinylpyridine)-block-polyethylene oxide (PS-b-P2VP-b-PEO) was achieved by intramolecular crosslinking via complexation of P2VP with cobalt octacarbonyl, while the metallic complex was incorporated within the crosslinked core. It is crucial to introduce electrostatic interaction along the chain by pretreatment and thus ensure the intramolecular crosslinking in concentrated solutions, for example, 30 mg/mL. After thermolysis in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
(58 reference statements)
1
27
0
2
Order By: Relevance
“…In an interesting work by Yang and co‐workers, SCJNPs with magneto‐responsive properties were synthesized in two steps. [ 8 ] In the first step, the triblock copolymer polystyrene‐block poly(2‐vinylpyridine)‐block‐polyethylene oxide (PS‐ b ‐P2VP‐ b ‐PEO) was pre‐treated by Co 2 (CO) 8 /THF complex to form electrostatic medium ( Figure ). This pre‐treatment provided the possibility to perform the intramolecular crosslinking in high concentration (20 mg mL −1 ).…”
Section: Scnps Via Metal Coordinationmentioning
confidence: 99%
See 2 more Smart Citations
“…In an interesting work by Yang and co‐workers, SCJNPs with magneto‐responsive properties were synthesized in two steps. [ 8 ] In the first step, the triblock copolymer polystyrene‐block poly(2‐vinylpyridine)‐block‐polyethylene oxide (PS‐ b ‐P2VP‐ b ‐PEO) was pre‐treated by Co 2 (CO) 8 /THF complex to form electrostatic medium ( Figure ). This pre‐treatment provided the possibility to perform the intramolecular crosslinking in high concentration (20 mg mL −1 ).…”
Section: Scnps Via Metal Coordinationmentioning
confidence: 99%
“…Reproduced with permission. [ 8 ] Copyright 2020, American Chemical Society.…”
Section: Scnps Via Metal Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2018 Wiley. (D) Synthesis of single-chain Janus composite nanoparticle from PEO- b -P2VP- b -PS . Adapted with permission from ref .…”
Section: Scnp With Novel Topologiesmentioning
confidence: 99%
“…[20][21][22] It is reported that the poly (vinylpyridine) (PVP)-containing polymers were successfully intramolecularly crosslinked by the metallic ion of Cu 2+ and metallic complex of Co 2 (CO) 8 . 23,24 However, the crosslinked PVP segments lack active groups for further modification. On the other hand, carboxylic acid-containing polymers should be promising precursors to derive metal-containing SCNPs.…”
Section: Introductionmentioning
confidence: 99%